The Effect of Music Instrument Kacapi Suling "Ayun Ambing" Towards Reducing Blood Pressure of Hypertension - Irma Herliana; Uswatun Hasanah; Dewi Arianti (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Hypertension is still the most common complaint in Indonesia. Apart from causing some discomfort, complications of hypertension are also considered to be life-threatening. One therapy that can be used to lower blood pressure is music therapy. Kacapi suling is one of the traditional Sundanese music that is popular among the Sundanese people with a frequency of 50–75 Hz, 121 Kilobytes per second (Kbps), 76 decibels with a slow tempo. Objective: This study aims to find out the effect of kacapi suling instrument music therapy on blood pressure in hypertensive patients. Methods: This study used a Pre-Experimental Design in the form of a One-Group Pretest-Posttest with 20 respondents with hypertension. Data collection tools in the form of a sphygmomanometer, a questionnaire containing the respondent's biodata, gadgets, loudspeakers, and stationery. Instrumental music is played once with a duration of approximately 5 minutes using a device connected to a loudspeaker. Before and after blood pressure measurements were taken. Data analysis in this study using Wilcoxon. Results: The results showed that the average systolic pre-test score was 142.86 while the post-test average was 135.24 with a p-value = 0.001. The average post-test diastolic value was 87.62 and the average post-test score was 84.29 with a p-value = 0.122. Conclusion: There is an effect of kacapi suling “Ayun Ambing: instrument music on decreasing systolic blood pressure in hypertensive patients but there is no effect on diastolic blood pressure.